Mental Health Spillover Effects Among Cohabitating Caregivers of Sierra Leonean Youth Receiving a Cognitive Behavioral Therapy‐Based Intervention. (15th September 2021) - Desrosiers, Alethea; Schafer, Carolyn; Freeman, Jordan; Vandi, Alpha; Hinton, Miriam; Betancourt, Theresa
Abstract : Research Objective: Evidence‐based mental health interventions have helped address health services gaps, but their reach and societal benefit can be limited in low resource settings. This study extends a scale‐up study of a cognitive behavioral therapy (CBT)‐based intervention, the Youth Readiness Intervention (YRI), among high‐risk youth in post‐conflict Sierra Leone to investigate potential household spillover effects of the YRI among cohabitating caregivers of youth who received the intervention. Study Design: A mixed methods approach was used to examine mental health spillover effects to cohabitating caregivers. We recruited YRI index (N = 165) and control index participants (N = 164). Index participants nominated their primary cohabitating caregiver (e.g., person who cares most for them). We then recruited and enrolled cohabitating caregivers of YRI and control index participants (N = 286) and administered quantitative assessments on mental health (e.g., depression, anxiety), emotion regulation, functional impairment, and caregiver sense of burden at baseline and 12‐month follow‐up. Changes in mental health and caregiver burden among YRI index participants' caregivers and control index participants' caregivers will be compared over time using linear growth modeling. Nineteen key informant interviews were also conducted with caregivers of YRI index participants at baseline and 12 month follow‐up to explore how spillover effects might occur. Qualitative data was analyzed using grounded theory. Two trained team members independently coded 10% of transcripts until 80% reliability was achieved, and then coded the full data set using the robust coding scheme. Population Studied: Sierra Leonean youth in three rural districts aged 18–30 and adult caregivers aged 18 and over. Principal Findings: Qualitative results identified several themes, including behavioral changes in index participants, improved relations between index participants and caregivers, and improved mood in caregivers. Improvements in interpersonal relationships between index participants and caregivers were related to reduced sense of caregiving burden, improved household dynamics, and caregivers' overall perceptions of index participants. Caregivers reported that they thought the changes in index participants occurred through an increased commitment to their education and improvements in their mood and interpersonal relationships. Caregivers also noted an increase in their own sense of happiness. Results of quantitative analyses have been consistent with the qualitative findings. Conclusions: YRI participation in an evidence‐based group mental health intervention has implications for improved relationships between index participants and their cohabitating caregivers. Cohabitating caregivers of youth who participated in the YRI may experience indirect benefits of the intervention, including a reduced sense of caregiver burden. The evidence supporting positive mental health spillover effects of the YRI suggests evidence‐based interventions for youth have additional benefits for household members and warrants further attention in future research on investment analyses. Implications for Policy or Practice: Understanding mechanisms of spillover occurring in the YRI may help address the challenge of delivering innovative, evidence‐based health and mental health interventions with sufficient breadth and depth to benefit large populations in Sierra Leone and other low‐resource settings. Providing evidence of measurable spillover effects of mental health interventions in low resource settings has the potential to galvanize new investments in large‐scale mental health initiatives. Primary Funding Source: National Institutes of Health.